2013
DOI: 10.3177/jnsv.59.100
|View full text |Cite
|
Sign up to set email alerts
|

Is Plasma Alpha-Tocopherol Associated with Electronegative LDL in Obese Adolescents?

Abstract: Summary Obesity has increased in children and adolescents. What is reflected in the early occurrence of cardiometabolic alterations, like hypertension and type 2 diabetes, where the oxLDL formation is stimulated. Various studies have shown that plasma a-tocopherol (a-TP) can protect LDL against oxidation. Nevertheless, the action of plasma a-TP in cardiovascular diseases remains controversial. We conducted a cross-sectional study to evaluate plasma a-TP and its impact on the concentration of LDL(2). Adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
1
9
0
2
Order By: Relevance
“…Increased proportions of electronegative LDL have been described in many conditions that define metabolic syndrome, such as hypertriglyceridemia [10], diabetes [4,11], insulin resistance [12], obesity [13], and hypertension [14]. Previously, we separated plasma LDL according to charge into 5 subfractions, L1-L5, by using anion-exchange chromatography and showed that plasma levels of L5—the most electronegative subfraction of LDL—are higher in patients with MetS and ST-segment elevation myocardial infarction (STEMI) than in healthy individuals [15].…”
Section: Introductionmentioning
confidence: 99%
“…Increased proportions of electronegative LDL have been described in many conditions that define metabolic syndrome, such as hypertriglyceridemia [10], diabetes [4,11], insulin resistance [12], obesity [13], and hypertension [14]. Previously, we separated plasma LDL according to charge into 5 subfractions, L1-L5, by using anion-exchange chromatography and showed that plasma levels of L5—the most electronegative subfraction of LDL—are higher in patients with MetS and ST-segment elevation myocardial infarction (STEMI) than in healthy individuals [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have shown that LDL( − ) and α-tocopherol and retinol are inversely correlated. To date, these associations have not been reported in the literature although a relationship between LDL( − ) and α-tocopherol was previously observed in obese adolescents, 34 patients submitted to haemodialysis 35 and subjects with dyslipidaemia. 36 Delimares et al 37 observed that the oxLDL generation was associated with an increased risk of breast cancer (odds ratio = 1.02, 95% confidence interval = 1.001-1.031), suggesting that elevated oxLDL levels, indicating the involvement of lipid peroxidation, can lead to higher oxidative stress.…”
Section: Discussionmentioning
confidence: 93%
“…The LDL particles can be modified, resulting in a more electronegative LDL subfraction with oxidised characteristics 39 and proinflammatory properties. 40 Previously, we proposed that LDL( − ) is a potential early biomarker for oxidative stress; 34 this likelihood could be reinforced by their antibodies anti-LDL( − ). The present study confirms that women with breast cancer are in oxidative stress and show modified particles with different levels of oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have shown that LDL(-) and -tocopherol and retinol are inversely correlated. To date, these associations have not been reported in the literature although a relationship between LDL(-) and -tocopherol was previously observed in obese adolescents (30), submitted to hemodialysis (31) and dyslipidemia (32).…”
Section: Ros (H 2 O 2 and O 2 -mentioning
confidence: 93%